The effect of selected kinematic variables on the accuracy of topspin forehand among table tennis players - Alkhawaldeh, I. M. (International Journal of Human Movement and Sports Sciences, 2022)
This study aimed to identify the effect of selected kinematic variables on the accuracy of the topspin forehand among table tennis players. The study sample consisted of (8) male players who play in the Jordanian First Division Table Tennis League; (age= 23.74 ± 1.72 years, mass=71.22 ± 11.21 kg, height=1.74 ± 0.10 m). The study used A (Canon EOS 80D) camera, which has a speed of (500) images per second, and Kinovea (0.8.15) program was used to analyze the movements. The shooting accuracy test was also used to reach the accuracy of Forehand Topspin shooting. The results of the statistical analysis confirmed the acceptance of the main hypothesis of the study, which states that there is a statistically significant impact of the selected kinematic variables on the accuracy of the topspin forehand at (a=0.05). The results also showed the acceptance of three sub-hypotheses, which state that there is a statistically significant impact at (a=0.05) of shoulder's angular velocity, wrist angle and racket's horizontal velocity on the accuracy of the topspin forehand. In light of the results, the study recommended the necessity of urging table tennis coaches in the Jordanian league to develop an appropriate mechanical kinematic model for each player when performing the skill of the forehand topspin.